The Role of Forensic Accounting in Detecting Financial Fraud in Public Sector Organizations - Novalia Herlina Bleskadit; Sukriyah; Nopi Hernawati; Loso Judijanto; Muhsin (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Financial fraud in public sector organizations remains a persistent challenge that threatens transparency, accountability, and public trust. Conventional auditing approaches often fail to detect complex and concealed fraudulent practices due to their compliance-oriented nature. This study aims to analyze the role of forensic accounting in detecting and preventing financial fraud in public sector organizations. Using a qualitative research design, this study employs a literature review method by analyzing relevant national and international journal articles, academic books, and institutional reports related to forensic accounting and public sector fraud. Data were collected through systematic searches in academic databases and analyzed using content and thematic analysis to identify patterns, roles, effectiveness, and implementation challenges of forensic accounting. The findings indicate that forensic accounting plays a critical role in uncovering financial fraud through investigative auditing techniques, forensic data analytics, and legally defensible evidence. Moreover, forensic accounting contributes to fraud prevention by strengthening internal controls, enhancing transparency, and creating a deterrent effect within public institutions. However, its effectiveness is constrained by limited professional expertise, inadequate technological infrastructure, weak regulatory frameworks, and political interference. This study concludes that institutionalizing forensic accounting practices is essential for improving public sector financial governance and reducing fraud risks.